I was hoping someone can show me the proof for V(y1-Y2) = V(y1)+V(y2)- 2 Cov(Y1,Y2) or V(y1+Y2) = V(y1)+V(y2)+ 2 Cov(Y1,Y2) I understand the proof for V(y1+Y2) = V(y1) + V(Y2) for independent but im having trouble inferring for the dependent.
Follow Math Help Forum on Facebook and Google+
Originally Posted by Chowder610 I was hoping someone can show me the proof for V(y1-Y2) = V(y1)+V(y2)- 2 Cov(Y1,Y2) or V(y1+Y2) = V(y1)+V(y2)+ 2 Cov(Y1,Y2) I understand the proof for V(y1+Y2) = V(y1) + V(Y2) for independent but im having trouble inferring for the dependent. but so: CB
Thank you
View Tag Cloud